CONCLUDING REMARKS - Humphrey, Tonkin (My University, 2014)
"This Higher Education Leaders' Forum has been extraordinarily informative and stimulating. For those of us coming from other countries and visiting Nazarbayev University for the first time, it has been educational in the best sense. Particularly memorable for me have been the following:..." - ...
Keywords: Research Subject Categories::SOCIAL SCIENCES::Social sciences::Education::International education; higher education, Kazakhstan; university rankings